A comparison of children's awareness of symbols of social class with that of the adults in Dagupan West Central School - Mejia, Julia (Gales) 1922- (1953)
The objectives of this study are: (1) to see if children are aware of social class, and (2) to determine what symbols they are conscious of when they are conscious of social class.
Typewritten.
Vita.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Child study